Classification of innovative enterprises depending on their strategic behavior - Nagy, Szabolcs; Pererva, P. G. (My University, 2021)
An original classification of innovative firms is proposed, based on the biological approach often used to classify innovative firms and the corresponding competitive strategies they profess.
Keywords: innovations; heuristics; intellectual property; strategic behavior